2022
DOI: 10.1002/ehf2.13829
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the liver fibrosis marker fibrosis‐5 index in patients with acute heart failure

Abstract: Aims Recently, liver fibrosis markers, such as the fibrosis-4 index (FIB-4), have been shown to be associated with prognosis in patients with heart failure. The fibrosis-5 (FIB-5) index, which assesses albumin, alkaline phosphatase, aspartate transaminase, alanine aminotransferase and platelet count, is a simple liver fibrosis marker that was reported to be superior to FIB-4 for differentiation of liver fibrosis. This study aimed to compare the prognostic value of FIB-4 and FIB-5 in patients with heart failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…In young patients, the value of the FIB4 will tend to be relatively low score even if their liver dysfunction is high grade. Whether their result could apply to younger patient population is still unknown because the study populations in previous studies which evaluated the prognostic value of the FIB4 in patients with cardiovascular diseases mainly included elderly patients [13][14][15][16][17]20]. At this point, the FIB5 might be efficient to apply versatilely because its calculation formula does not include age.…”
Section: Comparison the Prognostic Values Between The Fib5 And The Fib4mentioning
confidence: 99%
“…In young patients, the value of the FIB4 will tend to be relatively low score even if their liver dysfunction is high grade. Whether their result could apply to younger patient population is still unknown because the study populations in previous studies which evaluated the prognostic value of the FIB4 in patients with cardiovascular diseases mainly included elderly patients [13][14][15][16][17]20]. At this point, the FIB5 might be efficient to apply versatilely because its calculation formula does not include age.…”
Section: Comparison the Prognostic Values Between The Fib5 And The Fib4mentioning
confidence: 99%
“…Previous cross-sectional studies and meta-analyses have reported that CAC scores reflect CAD severity and are associated with adverse cardiovascular outcomes. [38][39][40] Park et al also reported a significant association between liver fibrosis and coronary artery calcification development. 15 Therefore, we conducted further analysis and found that FIB-4 score and NFS were directly correlated with CAC scores, consistent with a previous study.…”
mentioning
confidence: 93%
“…Recently, the fibrosis-5 (FIB-5) [ 14 ] index using albumin, alkaline phosphatase (ALP), aspartate aminotransferase(AST)/alanine aminotransferase (ALT) ratio, and PLT count has been shown to be superior to the FIB-4 index in predicting severe cirrhosis in patients with chronic hepatitis B and C [ 15 , 16 ]. The FIB-5 index has better long-term prognostic value than the FIB-4 index as a valuable risk stratifier for the outcomes of cardiac death or rehospitalization in patients with AHF [ 17 ].…”
Section: Introductionmentioning
confidence: 99%